Mesozooplankton Graze on Cyanobacteria in the Amazon River Plume and Western Tropical North Atlantic - Conroy, Brandon J.; Steinberg, Deborah K.; Song, Bongkuen; Kalmbach, Andrew; Carpenter, Edward J.; Foster, Rachel A. (Frontiers in Microbiology, 2017)
Diazotrophic cyanobacteria, those capable of fixing di-nitrogen (N2), are considered one of the major sources of new nitrogen (N) in the oligotrophic tropical ocean, but direct incorporation of diazotrophic N into food webs has not been fully examined. In the Amazon River-influenced western tropical North Atlantic (WTNA), diatom diazotroph associations (DDAs) and the filamentous colonial diazotrophs Trichodesmium have seasonally high abundances. We sampled epipelagic mesozooplankton in the Amazon River plume and WTNA in May-June 2010 to investigate direct grazing by mesozooplankton on two DDA populations: Richelia associated with Rhizosolenia diatoms (het-1) and Hemiaulus diatoms (het-2), and on Trichodesmium using highly specific qPCR assays targeting nitrogenase genes (nifH). Both DDAs and Trichodesmium occurred in zooplankton gut contents, with higher detection of het-2 predominantly in calanoid copepods (2.33-16.76 nifH copies organism-1). Abundance of Trichodesmium was low (2.21-4.03 nifH copies organism-1), but they were consistently detected at high salinity stations (>35) in calanoid copepods. This suggests direct grazing on DDAs, Trichodesmium filaments and colonies, or consumption as part of sinking aggregates, is common. In parallel with the qPCR approach, a next generation sequencing (NGS) analysis of 16S rRNA genes identified that cyanobacterial assemblage associated with zooplankton guts was dominated by the non-diazotrophic unicellular phylotypes Synechococcus (56%) and Prochlorococcus (26%). However in two separate calanoid copepod samples, two unicellular diazotrophs Candidatus Atelocyanobacterium thalassa (UCYN-A) and Crocosphaera watsonii (UCYN-B) were present respectively, as a small component of cyanobacterial assemblages (< 2%). This study represents the first evidence of consumption of DDAs, Trichodesmium, and unicellular cyanobacteria by calanoid copepods in an area of the WTNA known for high carbon export. These diazotroph populations are quantitatively important in the global N budget, widespread and hence, the next step is to accurately quantify grazing. Nonetheless, these results highlight a direct pathway of diazotrophic N into the food web and have important implications for biogeochemical cycles, particularly oligotrophic regions where N2 fixation is the main source of new nitrogen.